2015
DOI: 10.1001/jamasurg.2014.2873
|View full text |Cite
|
Sign up to set email alerts
|

A Checklist-Based Intervention to Improve Surgical Outcomes in Michigan

Abstract: Importance Previous studies of checklist-based quality improvement interventions have reported mixed results. Objective To evaluate whether implementation of a checklist-based quality improvement intervention, Keystone Surgery, was associated with improved outcomes in patients undergoing general surgery in large statewide population. Design, Setting and Exposure Retrospective longitudinal study examining surgical outcomes in Michigan patients using Michigan Surgical Quality Collaborative clinical registry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(89 citation statements)
references
References 37 publications
2
87
0
Order By: Relevance
“…The power of peer communities comes from peer learning and tapping into intrinsic motivation among professionals (Dixon-Woods, Leslie, Tarrant, & Bion, 2013;Gould et al, 2015). This concept has not reaped rewards in others (Reames, Krell, Campbell Jr., & Dimick, 2015;Urbach, Govindarajan, Saskin, Wilton, & Baxter, 2014). To achieve success, some project-based initiatives, such as the CLABSI checklist, required major changes in teamwork and culture (Pronovost et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The power of peer communities comes from peer learning and tapping into intrinsic motivation among professionals (Dixon-Woods, Leslie, Tarrant, & Bion, 2013;Gould et al, 2015). This concept has not reaped rewards in others (Reames, Krell, Campbell Jr., & Dimick, 2015;Urbach, Govindarajan, Saskin, Wilton, & Baxter, 2014). To achieve success, some project-based initiatives, such as the CLABSI checklist, required major changes in teamwork and culture (Pronovost et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, researchers could not affect surgical outcome after introducing a checklist based quality program in a study including >64.000 patients from 14 participating centres in Michigan, USA [143]. The authors suspected a failure since their program was implemented in the operation room; in a heterogeneous group involving complex procedures and frequently changing personnel.…”
Section: Paper Iii: Point Prevalence Of Surgical Checklist Use In Europementioning
confidence: 99%
“…They suspect that such a complex environment is less susceptible for change. This may have complicated their successful implementation across the whole organisation [143].…”
Section: Paper Iii: Point Prevalence Of Surgical Checklist Use In Europementioning
confidence: 99%
“…37 In 2015, a dual disappointment was reported when a different research group in Michigan, using a surgical checklist modeled after that of Pronovost, found no improvements in infections, complications, or mortality among nearly 65 000 general surgery patients in 29 hospitals. 38 …”
Section: Negligible or No Differences In Outcomesmentioning
confidence: 99%